Potensi Penjatuhan Pidana Bagi Seseorang Yang Dengan Sengaja Menularkan Corona Virus Disease 2019 (Covid19) - Ramitha, I Made Mahatmajaya; Sarjana, I Made (Kertha Negara : Journal Ilmu Hukum, 2023)
ABSTRAK Tujuan studi ini untuk mengkaji kepastian hukum mengenai penjatuhan pidana bagi seseorang yang dengan sengaja menularkan CORONA VIRUS DISEASE 2019 (COVID-19). Corona Virus Disease 2019 atau yang biasa disebut COVID-19 telah dinyatakan oleh World Health Organisation (WHO) sebagai pandemic dan Pemerintah Indonesia berdasarkan Keputusan Presiden Nomor 11 Tahun 2020 tentang Penetapan Kedaruratan Kesehatan Masyarakat Corona Virus Disease 2019 (COVID-19). Kata Kunci: Kepastian Hukum, Pidana, COVID-19 ABSTRACT The purpose of this study is to examine legal certainty regarding criminal penalties for someone who intentionally transmits CORONA VIRUS DISEASE 2019 (COVID-19). Corona Virus Disease 2019 or commonly called COVID-19 has been declared by the World Health Organization (WHO) as a pandemic and the Government of Indonesia based on Presidential Decree Number 11 of 2020 concerning the Determination of Public Health Emergency Corona Virus Disease 2019 (COVID-19). Key Words: Legal Certainty, Criminal, COVID-19